Conversational Implicature: A Pragmatic Study of “Our Conversation” in Learning at University - Dalman,; Hesti,; Apriyanto, Sigit; Apriyanto, Sigit (International Journal of Psychosocial Rehabilitation, 2020)
The main target in conducting oral communication is actually how the speakers can understand the culture of the interlocutors, especially in terms of ways of thinking, patterns of life, work ethics, and beliefs adopted so that in turn the speakers of the language can use language by applicable social rules. This study aims to explain and describe the speech acts used by the lecturer and students in conversation during the Indonesia language teaching-learning process, and the intention contained behind conversations between lecturer and students in the Indonesia language teaching-learning process. This study used qualitative research methods. Data collection is done by listening and taking notes. The results of this study can be concluded that the lecturer and students use speech acts of locution, illocution, and perlocution in learning, and the objectives contained behind the speech of lecturer and students, among others: instruction, motivate, clarify, reinforce, entertain, and summarizing. Thus, lecturer and student conversations use direct and indirect speech acts in the Indonesia language teaching-learning process.